The enhanced removal of carbonaceous and nitrogenous disinfection by-product precursors using integrated permanganate oxidation and powdered activated carbon adsorption pretreatment. (December 2015) - Chu, Wenhai; Yao, Dechang; Gao, Naiyun; Bond, Tom; Templeton, Michael R.
Graphical abstract: Highlights: PM oxidation and PAC adsorption both improved the removal of DOC and DON compounds. PM oxidation has better performance on reducing HAA formation than PM adsorption. PAC adsorption has better performance on reducing N-DBP and THM formation than PM oxidation. PM improved the performance of PAC on removal of C-DBP and N-DBP precursors. PM–PAC process is a promising pretreatment technology in integrated control of DBPs. Abstract: Pilot-scale tests were performed to reduce the formation of a range of carbonaceous and nitrogenous disinfection by-products (C-, N-DBPs), by removing or transforming their precursors, with an integrated permanganate oxidation and powdered activated carbon adsorption (PM–PAC) treatment process before conventional water treatment processes (coagulation–sedimentation–filtration, abbreviated as CPs). Compared with the CPs, PM–PAC significantly enhanced the removal of DOC, DON, NH3 + –N, and algae from 52.9%, 31.6%, 71.3%, and 83.6% to 69.5%, 61.3%, 92.5%, and 97.5%, respectively. PM pre-oxidation alone and PAC pre-adsorption alone did not substantially reduce the formation of dichloroacetonitrile, trichloroacetonitrile, N-nitrosodimethylamine and dichloroacetamide. However, the PM–PAC integrated process significantly reduced the formation of both C-DBPs and N-DBPs by 60–90% for six C-DBPs and 64–93% for six N-DBPs, because PM oxidation chemically altered the molecular structures of nitrogenous organic compounds and increased the adsorption capacity of the DBP precursors, thus highlighting a synergistic effect of PM and PAC. PM–PAC integrated process is a promising drinking water technology for the reduction of a broad spectrum of C-DBPs and N-DBPs.